Molecular Endoscopy for the Diagnosis and Therapeutic Monitoring of Colorectal Cancer - Waldner, Maximilian J.; Neurath, Markus F. (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the leading causes of cancer related death in the western world. Its successful treatment requires early detection and removal of precursor lesions as well as individualized treatment of advanced disease. During recent years, molecular imaging techniques have shown promising results to improve current clinical practice. For instance, molecular endoscopy resulted in higher detection rates of precursors in comparison to conventional endoscopy in preclinical and clinical studies. Molecular confocal endomicroscopy allowed a further classification of suspect lesions as well as the prediction and monitoring of the therapeutic response. In this review, we summarize recent achievements for molecular imaging of CRC in preclinical studies, initial clinical trials and the remaining challenges for future translation into clinical practice.